Comparative evaluation of in vitro and in vivo high glucose-induced alterations in voltage-gated tetrodotoxin-resistant sodium channel: Effects attenuated by sodium channel blockers. (1st October 2015) - Kharatmal, S.B.; Singh, J.N.; Sharma, S.S.
Highlights: TTX-R INa activity was compared in diabetic and extra-cellular high glucose exposed DRG neurons. Sodium channel blockers exhibited concentration- and voltage-dependent inhibition of TTX-R INa in DRG neurons. Compounds like tetracaine and lidocaine actions may be explored in future against neuropathic pain. Present study describes the novel opportunities to target the neuropathic pain. Abstract: Glucose uptake in neurons depends on their cellular/physiological activity and the extracellular concentration of glucose around the cell. High concentration of extra-cellular glucose, as under hyperglycemic conditions or pathological condition in diabetes, may persist for extended periods of time in neurons and trigger cellular damage by altering voltage-gated sodium channels (VGSCs), the exact mechanism of which remains unclear. Therefore, we hypothesized that high glucose may directly affect kinetics of the VGSCs in the dorsal root ganglion (DRG) neurons. DRG neurons were exposed to normal glucose (NG: 5.5 mM) and high glucose (HG: 30 mM) for 24 h. In another set of experiments, diabetic DRG neurons were also isolated from streptozotocin-induced diabetic rats. Effects of sodium channel blockers on nociceptive parameters and tetrodotoxin-resistant (TTX-R) Na + channel kinetics were elucidated by whole-cell patch-clamp in HG exposure and diabetes-induced rat DRG neurons. HG exposure and diabetes-induced DRG neurons demonstrated significant increase in TTX-R Na + current (INa ) densities in comparison to the control. Both HG-exposed and diabetic DRG neurons demonstrated similar biophysical characteristics of INa . Lidocaine and tetracaine significantly decreased TTX-R INa density in a concentration- and voltage-dependent manner. Steady-state fast inactivation of INa was shifted in the hyperpolarizing direction whereas voltage-dependent activation was shifted in the rightward direction. Diabetic rats treated with lidocaine and tetracaine (3 mg/kg, i.p.) significantly improved thermal hyperalgesia, mechanical allodynia and motor nerve conduction velocity with a significant inhibition of TTX-R INa density as compared to the diabetic control. These results suggest that HG exposure increases the TTX-R Na + channel activity sensitive to Na + channel blockers, lidocaine and tetracaine.